2016
DOI: 10.1051/0004-6361/201629249
|View full text |Cite
|
Sign up to set email alerts
|

Dynamical analysis of the complex radio structure in 3C 293: clues on a rapid jet realignment in X-shaped radio galaxies

Abstract: Context. Radio galaxies classified as X-shaped/winged, are characterised by two pairs of extended and misaligned lobes, which suggest a rapid realignment of the jet axis, for which a potential cause (including binary supermassive black holes, a black hole merger, or a Lense-Thirring precession) is still under debate. Aims. Here we analyse the complex radio structure of 3C 293 winged source hosted by the post-merger galaxy UGC 8782, which uniquely displays a significant asymmetry between the sizes (and therefor… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
21
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 60 publications
3
21
0
Order By: Relevance
“…The estimated ⋆ e-mail: sumana@kth.se (SN) time-scale of episodic activity in 3C293 is ∼10 5 yr, which is significantly smaller than most other known DDRGs (Joshi et al 2011). In accordance with this, Machalski et al (2016) found that the outer lobes are ∼60 Myr old and that the jet activity related to the formation of the outer lobes ceased within the last Myr. Meanwhile, the misaligned inner lobes are only about ∼0.3 Myr old.…”
Section: Introductionsupporting
confidence: 79%
“…The estimated ⋆ e-mail: sumana@kth.se (SN) time-scale of episodic activity in 3C293 is ∼10 5 yr, which is significantly smaller than most other known DDRGs (Joshi et al 2011). In accordance with this, Machalski et al (2016) found that the outer lobes are ∼60 Myr old and that the jet activity related to the formation of the outer lobes ceased within the last Myr. Meanwhile, the misaligned inner lobes are only about ∼0.3 Myr old.…”
Section: Introductionsupporting
confidence: 79%
“…These include the following: (1) elliptical galaxies hosting XRGs have SMBHs of larger than average mass found using a control sample of elliptical galaxies (Mezcua et al 2011); and (2) detection of X-ray cavities and a likely stellar shell in the XRG system 4C +00.58 (Hodges-Kluck et al 2010b), as well as the detection of shells around the host galaxy of the XRG 3C 403 (Ramos Almeida et al 2011). Also, a recent dynamical analysis of the hybrid radio structural distortion observed in the radio galaxy 3C 293 lends support to the rapid jet realignment scenario for XRGs (Machalski et al 2016). On the other hand, the mergerinduced rapid reorientation model encounters difficulty in explaining the strong tendency for the wings of XRGs to align with the optical minor axis of the host galaxy (Gillone et al 2016, and references therein).…”
Section: Introductionmentioning
confidence: 72%
“…In the backflow model, the radio wings form owing to diversion of the backflowing lobe plasma, whose subsequent outward expansion is aided by the buoyancy forces exerted by a steep pressure gradient in the circumgalactic medium (CGM) of the parent galaxy (Leahy & Williams 1984;Worrall et al 1995;Kraft et al 2005;Miller & Brandt 2009), the diversion occurring preferentially into preexisting cavities/channels in the CGM (Leahy & Williams 1984;Machalski et al 2016). However, Leahy & Parma (1992) have cautioned that buoyancy-driven backflow cannot propagate faster than the external sound speed, and hence the wings propelled by the buoyancy forces are not expected to be longer than the main radio lobes (which are known to advance supersonically).…”
Section: Introductionmentioning
confidence: 99%
“…A few sources, for example, show some inner and outer lobes with a very high surface brightness contrast as observed in B2 0258+35 and for this reason are claimed to be restarted radio galaxies. Among these there are the radio galaxy associated with NGC 3998 (∼20 kpc, Frank et al 2016), the source 4C 29.30 (∼600 kpc, Jamrozy et al 2007), the misaligned DDRG 3C293 (190 kpc, Joshi et al 2011;Machalski et al 2016), the source Mrk 6 (7.5 kpc, Kharb et al 2006) and the well-known radio galaxy Centaurus A (∼200 kpc, McKinley et al 2018;Morganti et al 1999). Moreover, we note some similarity with the famous radio galaxies M87 (e.g.…”
Section: Comparison With Other Radio Galaxiesmentioning
confidence: 99%